Enhancing Scientific Literacy Skills: Development of Physics Teaching Materials based on Islamic Values - Nurwati, Nurwati; Abdullah, Helmi; Palloan, Pariabti (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2024)
This research aims to develop valid physics teaching materials based on Islamic values, assess their practicality, and analyze their effectiveness in improving scientific literacy skills. This research was conducted at MAN 2 Bulukumba with 27 eleventh-grade class A students and 9 physics teachers as practitioners. This research employed the 4D development model: define, design, develop, and disseminate. The materials' validity was evaluated using Aiken’s V, focusing on content, presentation, language, and graphics, and were deemed valid and suitable for use. Practitioners rated the materials as very practical across all assessed aspects. Effectiveness was analyzed through pre- and post-implementation tests of students’ scientific literacy, yielding an N-gain of 67% (effective criteria). The study concludes that physics teaching materials based on Islamic values are valid, practical, and effective in enhancing students' scientific literacy. Integrating Islamic values into physics learning strengthens students' understanding of scientific concepts while fostering a holistic perspective that connects science with spiritual and moral dimensions. This integration also increases students' motivation by demonstrating the relevance of physics to their religious teachings, making science learning more engaging. Furthermore, it facilitates contextual teaching of physics concepts, particularly in environments rich in Islamic values.